Association between vitamin D status and circulating myokines (irisin, myostatin, and myonectin) in children: A cross-sectional study - Muammer Buyukinan; Huseyin Kurku; Zafer Bagci; Yavuz Turgut Gederet; Ahmet Fatih Yilmaz (PLoS ONE, 2026)
Background Vitamin D is a pleiotropic hormone with regulatory functions that extend beyond bone and mineral metabolism to include skeletal muscle physiology. Skeletal muscle acts as an endocrine organ through the secretion of myokines, including irisin, myostatin, and myonectin, which participate in metabolic and musculoskeletal regulation. However, data regarding the association between vitamin D status and circulating myokines in children remain limited. Methods In this single-center, cross-sectional study, 43 children with vitamin D deficiency and 39 age- and sex-matched healthy controls were enrolled. Serum concentrations of 25-hydroxyvitamin D [25(OH)D], parathyroid hormone (PTH), mineral metabolism parameters, and circulating levels of irisin, myostatin, and myonectin were measured. Participants were additionally categorized according to PTH status. Between-group comparisons, correlation analyses with false discovery rate (FDR) correction, and multivariable regression analyses were performed. Results Children with vitamin D deficiency exhibited significantly lower median circulating levels of irisin (13.76 vs. 29.52 ng/mL), myostatin (363 vs. 1108 ng/L), and myonectin (2.24 vs. 5.28 ng/mL) compared with controls (all p < 0.05). In correlation analyses adjusted using the false discovery rate method, no significant associations between 25(OH)D and circulating myokines were observed in the vitamin D–deficient group, whereas positive correlations between 25(OH)D and both irisin and myonectin were identified in the control group. In multivariable regression models adjusted for age, sex, and BMI SDS, serum 25(OH)D remained independently associated with circulating irisin, myostatin, and myonectin levels. In analyses stratified by PTH status, myostatin and myonectin levels were lower in children with elevated PTH, whereas irisin did not differ significantly. Conclusions Vitamin D deficiency in childhood is associated with reduced circulating concentrations of muscle-derived myokines. These findings suggest a link between the vitamin D–PTH axis and muscle endocrine signaling during growth. Given the cross-sectional design, causal relationships cannot be inferred, and longitudinal studies are warranted.